The effect of Nigella sativa and vitamin D3 supplementation on the clinical outcome in COVID-19 patients: A randomized controlled clinical trial - Said, Shimaa A.; Abdulbaset, Alsayyed; El-Kholy, Amal A.; Besckales, Osama; Sabri, Nagwa A. (Frontiers in Pharmacology, 2022)
Background: The coronavirus disease 2019 (COVID-19) is a novel coronavirus that causes a severe respiratory infection. Since the immune status plays an essential role to combat COVID-19, herbal medicines, which have an immunomodulatory effect, may prevent and even treat COVID-19. Nigella sativa is one of the herbal medicines with antiviral and immunomodulatory activities and its therapeutic effectiveness suggested it is a candidate for its use as an add-on therapy in COVID-19. In addition, Vitamin D3 has an immunomodulatory role but the effect of therapeutic Vitamin D3 supplementation in SARS-CoV-2 infection is still not well known. Objective: To investigate the effect of Nigella sativa and Vitamin D3 as single supplementation and in a combination on viral clearance indicated by a negative polymerase chain reaction and the alleviation of symptoms during the study follow-up duration of 14 days. Results: Nigella sativa /Vitamin D3 combination added to the standard therapy of COVID-19 infections significantly contributed to the alleviation of most COVID-19 disease' signs and symptoms as follows; 50% of patients were free of cough after 7 days, 70% showed an absence of fatigue after 4 days, 80% showed no headache after 5 days, while, 90% were free of rhinorrhea after 7 days and 86.7% of the patients had no dyspnea after 7 days. Moreover, patients in the four studied groups showed a reduced median temperature after 3 days of treatment. Negative results of the polymerase chain reaction (PCR) test recorded on the seventh and fourteenth day of therapy were superior in the Nigella sativa/Vitamin D3 combination arm compared to the other studied arms where the value of the odd ratio (OR) on the seventh day was 0.13, 95% CI: 0.03-0.45, and that of the fourteenth day was 14: 0.09, 95% CI: 0.02-0.3. Conclusion: a promising therapeutic benefit of the administration of Nigella sativa and Vitamin D3 combination in COVID-19 patients with mild to moderate symptoms was observed. Additionally, the remarkable viral clearance in a short time interval and reduction in the severity and progression of symptoms recommended the use of this combination as an add-on therapy for the management of COVID-19 patients.